A triple‐blind, placebo‐controlled randomised trial of the ilioinguinal‐transversus abdominis plane (I‐TAP) nerve block for elective caesarean section1. (29th January 2018) - Staker, J. J.; Liu, D.; Church, R.; Carlson, D. J.; Panahkhahi, M.; Lim, A.; LeCong, T.
Summary: This study investigated the efficacy of a new ilioinguinal‐transversus abdominis plane block when used as a component of multimodal analgesia. We conducted a prospective, triple‐blind, placebo‐controlled randomised study of 100 women undergoing elective caesarean section. All women had spinal anaesthesia with hyperbaric bupivacaine, 15 μg fentanyl and 150 μg morphine, as well as 100 mg diclofenac and 1.5 g paracetamol rectally. Women were randomly allocated to receive the ilioinguinal‐transversus abdominis plane block or a sham block at the end of surgery. The primary outcome was the difference in fentanyl patient‐controlled analgesia dose at 24 h. Secondary outcomes included postoperative pain scores, adverse effects and maternal satisfaction. The cumulative mean (95%CI) fentanyl dose at 24 h was 71.9 (55.6–92.7) μg in the ilioinguinal‐transversus abdominis group compared with 179.1 (138.5–231.4) μg in the control group (p < 0.001). Visual analogue scale pain scores averaged across time‐points were 1.9 (1.5–2.3) mm vs. 5.0 (4.3–5.9) mm (p = 0.006) at rest, and 4.7 (4.1–5.5) mm vs. 11.3 (9.9–13.0) mm (p = 0.001) on movement, respectively. Post‐hoc analysis showed that the ilioinguinal‐transversus abdominis group was less likely to use ≥ 1000 μg fentanyl compared with the control group (2% vs. 16%; p = 0.016). There were no differences in opioid‐related side‐effects or maternal satisfaction with analgesia. The addition of the ilioinguinal‐transversus abdominis plane block provides superior analgesia to our usual multimodal analgesic regimen.